Propriedades Sísmicas Anisotrópicas Derivadas da Orientação Cristalográfica Preferencial de Muscovita-Quartzo Milonitos - MORALES, LUIZ; FERNANDES, LUÍS (Pesquisas em Geociências, 2007)
<!– .p text-align: justify; –> Seismic wave propagation in organized matter usually results in azimuthal variations of longitudinal waves (Pwaves), as well as the effect of birefringence in transversal waves (S-waves), which results in two orthogonal shear waves with contrasting velocities. In this paper we present the results of the anisotropic seismic properties of five samples of muscovitequartz mylonites collected in different parts of a fold in the Saas Fee region, Western Internal Alps. The P-wave velocities in these rocks varies from 5.73 to 6.32 km/s, whereas the high-velocity shear wave (S1) varies from 3.82 to 4.22 km/s and the low velocity (S2) from 3.73 to 4.09 km/s. The anisotropy in these rocks is relatively high and reaches values from 9.5% for P-waves, and almost 11% for shear wave splitting. Both anisotropy and propagation directions seem to be related to from the strong preferred orientation of quartz and muscovite but also depend of muscovite modal content within the different specimens. Development of preferred orientation of minerals destroys and disperses the single crystal seismic properties, which causes a decrease of wave velocities and a dispersion of propagation directions, of both compressional and shear waves. Since the preferred orientation of quartz and muscovite can be directly related to the main macroscopic structures in these rocks (foliation, lineation, and pole of foliation) and the anisotropic seismic properties are related to the preferred orientation, it is possible to determine the propagation directions in terms of these structures. Due to the relatively high muscovite content, many of the maximum propagation velocities are parallel/subparallel to the foliation and some parallel to the lineation of the reference frame. On the other hand, directions of minimum propagation cannot be directly related to the foliation pole. The presence of folds in the mid-to lower crust can exert changes in the propagation directions due to the foliation variation around such structures, mainly in the P-waves.